2021
DOI: 10.1016/j.ymgmr.2021.100809
|View full text |Cite
|
Sign up to set email alerts
|

Valine metabolites analysis in ECHS1 deficiency

Abstract: Short-chain enoyl-CoA hydratase (ECHS1) is involved in amino acid and fatty acid catabolism in mitochondria and its deficiency causes Leigh syndrome or exercise-induced dystonia. More than 60 patients with this condition have been reported till date. The accumulation of intermediate metabolites of valine is assumed to be responsible for the cytotoxicity. Since protein restriction, including valine reportedly improves neurological symptoms, it is essential to consider the possible incidence of and diagnose ECHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Targeted analysis was unsuccessful in confirming the identity of acrylyl-CoA due its high reactivity. Alternatively, the presence of acrylyl-CoA was confirmed following the detection of S-(2-carboxyethyl) cysteine (SCEC), a conjugate formed following the spontaneous reaction between acrylyl-CoA and the sulfhydryl group of cysteine (52). Hepatic SCEC levels increased 15.6-fold following oral gavage of male mice with 30 μg/kg TCDD every 4 days for 28 days ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted analysis was unsuccessful in confirming the identity of acrylyl-CoA due its high reactivity. Alternatively, the presence of acrylyl-CoA was confirmed following the detection of S-(2-carboxyethyl) cysteine (SCEC), a conjugate formed following the spontaneous reaction between acrylyl-CoA and the sulfhydryl group of cysteine (52). Hepatic SCEC levels increased 15.6-fold following oral gavage of male mice with 30 μg/kg TCDD every 4 days for 28 days ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic SCEC levels increased 15.6-fold following oral gavage of male mice with 30 μg/kg TCDD every 4 days for 28 days ( Table 1 ). Urine cysteine/cysteamine conjugates with acrylyl-CoA are routinely used to diagnose Leigh syndrome where the conversion of acrylyl-CoA to 3-hydroxypropionyl-CoA is inhibited due to a deficiency in the short chain enoyl-CoA hydratase (ECHS1) activity (52). The increased levels of SCEC not only confirmed acrylyl-CoA accumulation but also ECHS1 inhibition, and that propionyl-CoA was metabolized via the alternate Cbl-independent β–oxidation-like pathway as opposed to the preferred Cbl-dependent carboxylation pathway (53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time, no isoleucine supplementation was necessary, as isoleucine and leucine levels were within the normal range, showing results similar to those described by Abdenur et al [ 3 ]. Recently, Kuwajima et al reported that protein restriction therapy may alleviate the symptoms of ECHS1 deficiency [ 37 ]. A low-protein diet may prevent disease progression, while a valine-restricted diet may lead to a clinical and neuroradiological improvement in ECHS1 deficiency [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ectonucleotide pyrophosphatase/phosphodiesterase3 (ENPP3), as a regulator of N-acetylglucosaminyltransferase GnT-IX (GnT-Vb), would have widespread and significant impacts on glycosyltransferase activities [26]. Short-chain enoyl-CoA hydratase (ECHS1) is involved in amino and fatty acid catabolism in mitochondria and its deficiency results in Leigh syndrome or exercise-induced dystonia [27]. Niemann-Pick C1-Like 1 (NPC1L1) was widely verified to be a cholesterol import protein and mediated intestinal cholesterol absorption [28].…”
Section: Discussionmentioning
confidence: 99%